DEVELOPMENT OF DIGITAL COMICS WITH THE HELP OF CANVA ON FOOD WEB MATERIAL FOR CLASS V STUDENTS: PENGEMBANGAN KOMIK DIGITAL BERBANTU CANVA PADA MATERI JARING-JARING MAKANAN UNTUK SISWA KELAS V - Tirta Nurani; Laili Rahmi (SOSIOEDUKASI, 2025)
This study aims to develop innovative learning media in the form of Canva-assisted digital comics on food web material for fifth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model which is limited to the Development stage . The research subjects consisted of material experts, media experts, and linguists. The research procedure started from the stages of Needs Analysis, Storyboard Design, and Product Development using the Canva application. The resulting product was then validated by material experts and media experts using a feasibility questionnaire instrument. Qualitative data (input and suggestions) were analyzed descriptively, while quantitative data (percentages) were analyzed using a Likert scale. The validation results showed that this digital comic media had a very high level of validity. Assessments from material experts were in the range of 87.5%-100% and media experts in the range of 93.75%-100%, both of which were included in the "Very Valid" category. Validation results from linguists showed that Canva-assisted digital comic products on food web material had a very high level of validity. All assessed aspects scored above 87%, indicating the product is suitable for use without major revisions . Therefore, the developed digital comic is highly suitable and can be used as an effective, engaging learning medium that meets student needs and the curriculum.